Modelling Situated Actions in Collaborative Hypertext Databases - Chen, Chaomei; Rada, Roy (Oxford University Press, 2020)
The need to model users' dynamic behaviour in Computer Supported Cooperative Work (CSCW) systems arises in many contexts. This study developed a probabilistic model of the usage of an awareness-maintaining mechanism in a collaborative hypertext database system. Longitudinal time series data of user-database interaction were studied. The study found that the recurring patterns in the occurrences of the awareness-seeking event were related to several contextual aspects of the CSCW system studied. The context-behaviour relationship is captured by a Poisson regression model. The analytical method can be applied to the study of situated actions in other CSCW systems.
Keywords: modelling users' dynamic behavior; Supported Cooperative Work (CSCW) systems; collaborative hypertext database system